Recruiting and Retaining STEM Teachers in Rural Areas in Lebanon - Zebian, Farah (2022)
Educational leaders in rural areas struggle to recruit and retain highly qualified teachers. Compared to schools in urban and suburban areas, educational leaders in rural areas have difficulties staffing their classrooms with qualified teachers, especially in STEM fields, because of teacher shortage. The purpose of this study was to explore the challenges that educational leaders face in recruiting and retaining qualified STEM teachers in rural areas in Lebanon and the strategies that they use. This qualitative study used grounded theory and focused on the lived experiences of 21 educational leaders of three schools located in rural areas in Lebanon. Questionnaires, interviews, and a researcher journal were used as data sources. To overcome teacher shortage and burnout, the school leaders reported four major challenges that influenced recruiting and retaining qualified teachers: low salaries, underqualified teacher candidates, insufficient educational resources, and low performing students. School leaders noted that successful strategies in recruiting and retaining qualified teachers included: attracting teachers to work in rural areas, recruiting qualified teachers, and maintaining a productive and positive teaching and learning environment. This study added to the existing literature through focusing on the lived experiences of school leaders in Lebanon as well as highlighting the challenges and strategies unique for the Lebanese cultural context.